Responses of salivary cortisol and a-amylase to official competition - Azarbayjani, M. A.; Dalvand, H.; Fatolahi, H.; Hoseini, S. A.; Farzanegi, P.; Stannard, S. R. (Journal of Human Sport & Exercise, 2011)
This study was designed to determine the relationship between salivary cortisol, á-amylase and total protein response in the official football players during the course of a game. Nine young amateur football players agreed to participate in the study. Saliva samples were collected from each player 30 min and 5 min before the start of the competition, at half time, and then again 5 and 30 min after the end of competition. A significant increase in cortisol (p=0.04) in response to playing the competition was observed including a significantly higher concentration 30 min after match as compared to half time (p=0.016). In contrast, changes in salivary á-amylase changes were irregular, but there was significant decline 5 min after end of match as compared to the 5 min before the beginning of match (p<0.019). No significant difference in total protein concentration was observed. Though salivary cortisol, á-amylase and total protein changes were observed concomitantly, but there no significant relationship between them. We conclude that participation in competition has an accumulative effect on salivary cortisol concentration, but this was not related changes in salivary á-amylase.